Concept and Implementation on the State of Emergency in Indonesia: Outlook to Strengthen Checks and Balances during Crisis - Ayuni, Qurrata; Arinanto, Satya; Arsil, Fitra; Indrati, Maria Farida (Revista de Investigações Constitucionais, 2022)
This paper analyzes the problems caused by the state of emergency in Indonesia. It focuses on explaining the meaning of a state of emergency, based on Article 12 of the 1945 Indonesian Constitution. It addresses how Indonesia determines the emergency status and how checks and balances regarding the emergency status were implemented. This paper highlights three points. First, the existing law on the state of emergency is no longer in line with Indonesia's constitutional concept, following the amendment; second, there are findings indicating that several emergency statuses were not appropriately declared; third, the lack of the Parliamentary and court role in conducting checks and balances on the President in the state of emergency. This paper offers a recommendation concerning the importance of strengthening checks and balances to ensure there will be no abuse of power in implementing a state of emergency in the future.